Determinants of Purchasing Decisions of Electric Vehicles (EVS) in Kathmandu Valley - Kathbaniya, Rohan Das (Nepalese Journal of Economics, 2025)
The study examines the determinants of purchasing decisions of electric vehicles (EVs) in Kathmandu Valley. Consumer preference is dependent variable. The selected independent variables are financial attributes, technical attributes, charging availability, social influence and environment concern. The primary source of data is used to assess the opinions of respondents regarding financial attributes, technical attributes, charging availability, social influence and environment concern on consumer preference for electric vehicle in Kathmandu. The study is based on primary data of 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumer preference for electric vehicle in Kathmandu. The study revealed that various factors significantly influence consumer preference for purchasing electric vehicles (EVs) in Kathmandu Valley. An increase in financial attributes boosts consumer preference, indicating that favorable financial conditions make EVs more attractive to consumers. Improvements in technical attributes, such as advancements in range and performance, also increase consumer interest, suggesting that better technology makes EVs more appealing. Greater charging availability raises consumer preference, emphasizing the importance of accessible infrastructure. Enhanced social influence, through recommendations and trends within social circles, further increases consumer interest by making EVs more popular among peers. Additionally, a higher level of environmental concern increases consumer preference, indicating that greater awareness of environmental issues leads to a stronger inclination to choose EVs.